Pain therapy in patients with advance renal cancer. Pharmacology and invasive techniques - Sieńkowska-Magoń, Monika; Grzesiak, Joanna; Leś, Jarosław; Żukowski, Paweł; Brzozowski, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2005)
Cancer pain is a worldwide problem. It has been estimated that 65-85% patient with advanced cancer complain of moderate to severe pain. It has a major destructive impact on the quality of life in these patients. Good to excellent relief can be obtained in most patients with currently available modalities. The use of pharmacological agents is considered to be the mainstay of therapy for cancer pain but invasive procedures play an important role in selective cases. We have to remember that neuropathic pain very often present in cancer patient may be resistant to standard opioid therapies or other nociceptive pain treatment strategies there for anticonvulsants and antidepressants are the drugs of choice. Unfortunately many patients suffer pain due to misconceptions regarding use of opioids and cancer pain management. Knowledge of the indications and correct choice among the treatment options is crucial. Treating physical suffering we should not forget about patients psychological well-being. In this article we would like to present current state of pain treatment for patients with renal cancer. One of the problems in this setting is endangered renal failure and impact of it on the drug pharmacokinetic and pharmacodynamic. Most of the new cases are diagnosed in a late stage. By choosing proper therapy (type of analgesics, route of administration, epidural/spinal administration of opioids/local anaesthetics, neurolysis, adjuvants) we can make around 90% of our patients almost pain free. Close cooperation between different medical specialties cannot be over emphasized.